Morphological Study on Blood Cells of Mule - Mrigesh, Meena; Singh, Ishwar; Singh, Balwinder; Arora, Niddhi; Yadav, G. C. (Indian Journal of Veterinary Anatomy, 2017)
The study was conducted in ten normal apparently healthy mules from Kichha, Bara, Gular Bhoj and Gadarpur areas of Udham Singh Nagar District. The blood films were stained with the May Grunwald Giemsa Stain for general cytomorphology and New methylene blue stain for reticulocytes. The stained blood smears were examined under oil immersion objective (100X) lens to record the results. The erythrocytes of mule were non nucleated, round in shape and 6.25 ± 0.153mm in size. The reticulocytes observed were round in shape having different pattern of distribution of reticulin filaments. The neutrophils were round in shape and 12.25 ± 0.272mm in size with lobulated nucleus. The eosinophils were round in shape and 13.4 ± 0.245mm in size. The basophils were slightly larger than eosinophils (13.8 ± 0.270mm).The nuclei had 2-3 lobes placed eccentrically. The lymphocytes were round in shape with small, medium and large size. The monocytes were round in shape and measured 13.4 ± 0.195mm in size close in size to the donkey monocyte.